Management of Sustainable Palm Oil : The World Needs and Indonesian Commitment - Maskun; Ilmar, Aminuddin; Naswar; Achmad; Assidiq, Hasbi (International Journal of Psychosocial Rehabilitation, 2020)
The European Union has endorsed a draft proposal of energy which remove palm oil as the material basis of sustainable biofuels by 2021. It was done because the palm oil is considered as a cause of deforestation that increases the concentration of greenhouse gas emissions that cause global warming (climate change). This proposal is detrimental to Indonesia and shows injustice in the palm oil trade mechanism. This is inseparable from the position of Indonesia as one of the largest palm oil producers in the world and the value of palm exports which is quite significant for Indonesia. This paper will analyse Indonesian commitment related to the management of sustainable palm oil from the normative concept, availability of adequate regulation, and implemented aspects in several Provincial/District/City. This article expects to provide the reason for Indonesia to urge the European Union in order to receive the palm oil as a source of sustainable energy. The results of this article show Indonesia has had normative frame to manage sustainable palm oil. However, in implemented aspects including the Indonesian policy is considered still some weaknesses, in particular the issue of transparency and accountability.